Faktor-faktor yang Memoderasi Pengaruh Partisipasi Anggaran terhadap Senjangan Anggaran - Mita Puspita Sari; Restu Agusti; Al Azhar L (Jurnal Kajian Akuntansi dan Auditing, 2020)
This study aims to examine the effect of Budget Participation on Budgetary Slack with Information Asymmetry, Organizational Commitment, Group Cohesiveness and Environmental Uncertainty as a moderating variables. The population in this study was 22 OPD Kuantan Singing Regency. In this study, the sample used is the 66 respondents were selected using purposive sampling method. This study used primary data by dissemination of the questionnaires. Technical analysis for test hypothesis that used in this study are simple regression analysis and Moderated Regression Analysis (MRA). Data collected from 60 respondents subsequently data were analyzed with the help of SPSS software version 17.0 using descriptive statistical analysis and simple linear regression analysis to produce classical assumption tests, data analysis models, coefficient of determination and prove hypotheses. The results of partial and simultaneous research found that the budgetary participation variable in budgetary slack with information asymmetry, organizational commitment, group cohesiveness and environmental uncertainty as a moderating variable.